Assertion-Based Design - Foster, Harry D.; Krolnik, Adam C.; Lacey, David J. (Springer US : Imprint: Springer, 2005)
Chapter 3 Specifying RTL Properties 61 3. 1 Definitions and concepts 62 62 3. 1. 1 Property 3. 1. 2 Events 65 3. 2 Property classification 65 Safety versus liveness 66 3. 2. 1 3. 2. 2 Constraint versus assertion 67 3. 2. 3 Declarative versus procedural 67 3. 3 RTL assertion specification techniques 68 RTL invariant assertions 69 3. 3. 1 3. 3. 2 Declaring properties with PSL 72 RTL cycle related assertions 73 3. 3. 3 3. 3. 4 PSL and default clock declaration 74 3. 3. 5 Specifying sequences 75 3. 3. 6 Specifying eventualities 80 3. 3. 7 PSL built-in functions 82 3. 4Pragma-based assertions 82 3. 5 SystemVerilog assertions 84 3. 5. 1 Immediate assertions 84 3. 5. 2Concurrent assertions 86 3. 5. 3 System functions 95 3. 6 PCI property specification example 96 3. 6. 1 PCI overview 96 3. 7 Summary 102 Chapter 4 PLI-Based Assertions 103 4. 1 Procedural assertions 104 4. 1. 1 A simple PLI assertion 105 4. 1. 2 Assertions within a simulation time slot 108 4. 1. 3 Assertions across simulation time slots 111 4. 1. 4 False firing across multiple time slots 116 4. 2 PLI-based assertion library 118 4. 2. 1 Assert quiescent state 119 4. 3 Summary 123 Chapter 5 Functional Coverage 125 5. 1 Verification approaches 126 5. 2 Understanding coverage 127 5. 2. 1 Controllability versus observability 128 5. 2.